Nano Based Approach for the Treatment of Neglected Tropical Diseases - Pandian, Sureshbabu Ram Kumar; Panneerselvam, Theivendren; Pavadai, Parasuraman; Govindaraj, Saravanan; Ravishankar, Vigneshwaran; Palanisamy, Ponnusamy; Sampath, Muthukumar; Sankaranarayanan, Murugesan; Kunjiappan, Selvaraj (Frontiers in Nanotechnology, 2021)
Neglected tropical diseases (NTDs) afflict more than one billion peoples in the world's poorest countries. The World Health Organization (WHO) has recorded seventeen NTDs in its portfolio, mainly caused by bacterial, protozoal, parasitic, and viral infections. Each of the NTDs has its unique challenges on human health such as interventions for control, prevention, diagnosis, and treatment. Research for the development of new drug molecules against NTDs has not been undertaken by pharmaceutical industries due to high investment and low-returns, which results in limited chemotherapeutics in the market. In addition, conventional chemotherapies for the treatment of NTDs are unsatisfactory due to its low efficacy, increased drug resistance, short half-life, potential or harmful fatal toxic side effects, and drug incompetence to reach the site of parasite infection. In this context, active chemotherapies are considered to be re-formulated by overcoming these toxic side effects via a tissue-specific targeted drug delivery system. This review mainly emphasizes the recent developments of nanomaterial-based drug delivery systems for the effective treatment of NTDs especially sleeping sickness, leishmaniasis, chagas disease, soil-transmitted helminthiasis, african trypanosomiasis and dengue. Nanomaterials based drug delivery systems offer enhanced and effective alternative therapy through the re-formulation approach of conventional drugs into site-specific targeted delivery of drugs.